ISLAMIC FINANCIAL PLANNING MASYARAKAT MUSLIM DI INDONESIA: ANALISIS FINANCIAL ATTITUDE, FINANCIAL KNOWLEDGE, DAN LOCUS OF CONTROL - Ismail Aziz, - (2021)
The fact that the Indonesian people just started financial planning at the age of 41 years becomes a serious problem for a person's life in the future. This study aims to determine the level of financial attitude, level of financial knowledge and level of locus of control in Muslim communities in Indonesia and their influence on Islamic Financial Planning. The approach in this study uses quantitative methods, which were analyzed by Partial Least Square-Structural Equation Modeling (PLS-SEM) and SmartPLS. The subject of this research is the Muslim community in Indonesia with a total sample of 380 respondents. The results showed that the level of financial attitude was in the high category, while the level of financial knowledge and the level of locus of control of the Muslim community was in the medium category. The variable level of financial attitude and level of financial knowledge has a positive influence on Islamic financial planning. While the locus of control level variable has no influence on Islamic Financial Planning. Thus, financial attitude and financial knowledge are important things to encourage someone to do Islamic financial planning. It is hoped that this research can grow and improve the climate in the financial industry, especially related to financial planning.